Divergence and Remarkable Diversity of the Y Chromosome in Guppies. (6th October 2020) - Almeida, Pedro; Sandkam, Benjamin A; Morris, Jake; Darolti, Iulia; Breden, Felix; Mank, Judith E
Abstract: The guppy sex chromosomes show an extraordinary diversity in divergence across populations and closely related species. In order to understand the dynamics of the guppy Y chromosome, we used linked-read sequencing to assess Y chromosome evolution and diversity across upstream and downstream population pairs that vary in predator and food abundance in three replicate watersheds. Based on our population-specific genome assemblies, we first confirmed and extended earlier reports of two strata on the guppy sex chromosomes. Stratum I shows significant accumulation of male-specific sequence, consistent with Y divergence, and predates the colonization of Trinidad. In contrast, Stratum II shows divergence from the X, but no Y-specific sequence, and this divergence is greater in three replicate upstream populations compared with their downstream pair. Despite longstanding assumptions that sex chromosome recombination suppression is achieved through inversions, we find no evidence of inversions associated with either Stratum I or Stratum II. Instead, we observe a remarkable diversity in Y chromosome haplotypes within each population, even in the ancestral Stratum I. This diversity is likely due to gradual mechanisms of recombination suppression, which, unlike an inversion, allow for the maintenance of multiple haplotypes. In addition, we show that this Y diversity is dominated by low-frequency haplotypes segregating in the population, suggesting a link between haplotype diversity and female preference for rare Y-linked color variation. Our results reveal the complex interplay between recombination suppression and Y chromosome divergence at the earliest stages of sex chromosome divergence.